2009
DOI: 10.1016/j.joca.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Vibration training intervention to maintain cartilage thickness and serum concentrations of cartilage oligometric matrix protein (COMP) during immobilization

Abstract: The results of this study suggest that articular cartilage thickness is sensitive to unloading and that vibration training may be a potent countermeasure against these effects. The sensitivity of cartilage to physical training is of high relevance for training methods in space flight, elite and sport and rehabilitation after illness or injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 37 publications
(43 reference statements)
5
76
0
1
Order By: Relevance
“…First, our results are in agreement with previous studies that reported a decrease in serum COMP concentration during rest, while in these studies the activity prior to the first blood sample was monitored (Andersson et al 2006;Mundermann et al 2005Mundermann et al , 2009. Second, the absolute COMP levels in our study are comparable to baseline levels in other studies after 15 min rest (Mundermann et al 2005) or unloading (Liphardt et al 2009). Third, the significant reduction in COMP levels persisted even over the following 7 h analysed in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, our results are in agreement with previous studies that reported a decrease in serum COMP concentration during rest, while in these studies the activity prior to the first blood sample was monitored (Andersson et al 2006;Mundermann et al 2005Mundermann et al , 2009. Second, the absolute COMP levels in our study are comparable to baseline levels in other studies after 15 min rest (Mundermann et al 2005) or unloading (Liphardt et al 2009). Third, the significant reduction in COMP levels persisted even over the following 7 h analysed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Both moderate walking (Mundermann et al 2005) and extensive running exercise (Kim et al 2009;Neidhart et al 2000) elevated the serum COMP concentration in healthy subjects. Moreover, in a bed rest study serum COMP concentration decreased after 24 h of immobilisation but returned to baseline levels after the subjects were mobile again (Liphardt et al 2009). The increase in serum COMP concentration was immediately after an exercise protocol and the return to the baseline level took 30 min after 30 min of walking (Andersson et al 2006;Mundermann et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have started to explore the possibility that WBV combined with exercise and physical therapies may offer benefits to patients with KOA, including muscle strength [8], balance control [9], and decreased self-perception of pain [9]. Additionally, previous studies found that mechanical stimulation not only increased matrix accumulation and decreased matrix metalloproteinase production in osteoarthritic chondrocytes [10], but also enhanced collagen and chondrogenic marker expression in normal cartilage [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Three studies addressed the effects of immobilization and activity on biomarkers [9-11] and are remarkable for their novelty and rigor. The first, a crossover trial of 5 individuals, studied the effects of 14 days of enforced immobilization in a 6 degree “head-down-tilt-bed-rest’ position, with and without 2 brief treatments (5 minutes) of whole body vibration [9].…”
Section: Introductionmentioning
confidence: 99%